2001
DOI: 10.1076/phbi.39.6.408.5880
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry and Antibacterial Activity of Senna alata Flower

Abstract: Phytochemistry and antibacterial potency of some crude and partially purified fractions of Senna alata flower was examined against 22 bacterial strains. The crude plant extracts, containing steroids, anthraquinone glycosides, volatile oils and tannins, exhibited a high minimum inhibitory concentration of 500 mg/mL against Staphylococcus aureus, Streptococcus faecalis, Micrococcus luteus, Bacillus subtilis and Pseudomonas putida, but was generally inactive against Escherichia coli, Proteus vulgaris, Pseudomonas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…Existing reports suggest its potential activity against fungi; however, its activity against bacteria was ambiguous with varying MIC values (Ibrahim and Osman ; Adedayo et al . ; Somchit et al . ; El‐Mahmood and Doughari ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing reports suggest its potential activity against fungi; however, its activity against bacteria was ambiguous with varying MIC values (Ibrahim and Osman ; Adedayo et al . ; Somchit et al . ; El‐Mahmood and Doughari ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the different plant parts, the leaves have higher use in traditional medicine compared to other parts. Existing reports suggest its potential activity against fungi; however, its activity against bacteria was ambiguous with varying MIC values (Ibrahim and Osman 1995;Adedayo et al 2001;Somchit et al 2003;El-Mahmood and Doughari 2008). In this study, anti-QS activity of Ca.…”
Section: Introductionmentioning
confidence: 99%
“…The crude S. alata fl ower extracts, containing steroids, anthraquinone glycosides, volatile oils and tannins, exhibited a high MIC of 500 μg/mL against Staphylococcus aureus, Streptococcus faecalis, Micrococcus luteus, Bacillus subtilis and Pseudomonas putida but was generally inactive against Escherichia coli, Proteus vulgaris, Pseudomonas aeruginosa, Serratia marcescens and Pseudomonas fl uorescens (MIC >1,000 μg/mL) (Adedayo et al 2001 ). However, the partially purifi ed fl ower extract was bacteriostatic at a low concentration of 100 μg/mL, with a minimum bactericidal concentration of 500 μg/mL, primarily against the Gram-positive organisms.…”
Section: In-vitro Studies Other Plant Part Extractsmentioning
confidence: 98%
“…Roxb (Leguminosae), known as Ringworm plant, winged senna, craw-craw plant or king of the forest, is of great importance in traditional medical practice in many developing countries [1]. In Nigeria, it is called 'Asunwon oyinbo' and 'Nelkhi' in the Western and Eastern regions of the country respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The whole plant is used in Brazil, Guatemala and Guinea in the treatment of malaria, flu and other infectious diseases [3]. Studies have also reported the antibacterial, antifungal and antiviral properties of S. alata leaf [1,6] as well as its laxative [3] and abortifacient properties in wistar rats [2]. Of particular interest is its use in the management of sugar-related disorders such as diabetes mellitus and hyperglycaemia [5][6][7].…”
Section: Introductionmentioning
confidence: 99%